Price and service competition with maintenance service bundling - Wang, Yi; Sun, Linyan; Qu, Rong; Li, Gang (Springer, 2015)
In many equipment manufacturing industries, firms compete with each other not only on products price, but also on maintenance service. More and more traditional products oriented firms are offering their customers products bundled with maintenance service (P&S bundles). In this study, we examine firms’ incentive to offer customers products bundling with long-term maintenance or repair support service in a duopoly competitive environment. When providing P&S bundles, a firm need to determine the service level (in terms of average response time guarantee for the service in this paper) to offer and needs to build a service facility to handle the maintenance service requirements. Based on the analysis of three sub-game models, we characterize the market conditions in which only one firm, both firms or neither firm will offer P&S bundles. Finally, we analyze the affects of several market factors on firms’ strategy choices.